Management of Nonunion of Tibia by Ilizarov Technique - Haque, MA; Islam, SM; Chowdhury, MR (Community Based Medical Journal, 2013)
This prospective study was carried out during the period of January 2007 to December 2011 in Mymensingh Medical College Hospital and other private clinics of Mymensingh town to assess the results of Ilizarov technice for nonunion of the tibia. Here total operated patient were 30, of them 24 were male and 6 were female. 10 cases are hypertrophic, 8 cases are atrophic and 12 cases are infected nonunion. In this series age of the patients was 10 ? 60 years. Motor vehicle accident was the commonest cause of fracture found in 66.67% cases. Second most common cause of injury was fall from height. Among 30 patients proximal corticotomy was done in 24 patient and distal corticomy in 2 patient. Union time was 4-12 months. Among 30 patients 27 were united at initial procedure. From nonunited 3 cases again refreshening of the ends along with bone grafting was done and ultimately 2 were united and 1 remains nonunited. In this series limb length discrepancy reduced to maximum 1.5 cm with contralateral limbs. Average total hospital stay was 15 days. Pin site infection and pain were the commonest complications in our study. Close adherences to Ilizarov principles make it now possible to successfully treat a most of orthopaedic conditions that previously were fraught with high morbidity rates and poor results. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16697 Community Based Medical Journal 2013 July: Vol.02 No 02: 41-45